Identity, professional identity and teacher identity: Theoretical-conceptual notes - Quirino, Raquel; Pinheiro, Antônia; Silvestre, Eliane; Herculano, Gissele Quirino (Seven Editora, 2024)
The categories of identity, professional identity, and professional teaching identity have historically been conceptualized from the perspectives of scholars of different nationalities, in specific approaches, and in various areas of knowledge. In view of the polysemy of the term "identity", it is necessary to situate the concepts in their various theoretical approaches in order to obtain a real meaning of what is meant when using it in academic studies and research. In the same way, the terms "professional identity" and "professional teaching identity", because they derive and are composed of and with the former, deserve the same treatment because they acquire different approaches in different theoretical contexts. Taking as a theoretical basis the productions of several scholars, in their studies on identity, professional identity and teacher identity – although the three terms have not been addressed by all of them – this article aims, based on a bibliographic review, to briefly discuss theoretical-conceptual notes of such categories. It is expected to subsidize researchers and scholars of the themes, with clues and references of exponent authors from different areas of knowledge and to achieve a greater understanding of these terms. DOI:https://doi.org/10.56238/sevened2024.010-067